Online Interactive Communication via Academic Blogging Activities Among Indonesian EFL Students - Shella Shafira Lubis; Budianto Hamuddin (REiLA : Journal of Research and Innovation in Language, 2019)
Indonesian people in the conversation using English in many ways, such as face to face and social media. The purpose of this research is to identify students' online interactive communication in their blog's comment. It focuses among students as Indonesian EFL students in Morphology class in Universitas Lancang Kuning (Unilak). This study also eager to know what type of language function and phase of knowledge construction on students blogging activities on selected IT platform classroom, i.e. Morphology blog course. The method employ in this research is a qualitative descriptive method. This study did take the comments' blog of all students in Morphology class, then this study analyzed the comments. The result of this research, students, showing some dominant type in Knowledge Construction, i.e., Sharing and Comparing of opinion in Blog. The present study also reveals the use of Expressing and Supporting Opinions as the dominant types in Language Function.